Concrete poles of transmission lines on the end of service life - Curovic, Nada (Journal of Applied Engineering Science, 2016)
Transmission system in Serbia, due to its age, inevitably enters the period of active investment project of reconstruction, adaptation and rehabilitation of the transmission lines. Today we are faced with the fact that the transmission lines are constructed more than 60 years ago, and are still in service. The paper discusses the problems in the implementation of projects of rehabilitation of reinforced concrete transmission line route. The results of experimental research, load test of reinforced concrete poles are show. It explains the problems in the management of investment projects of rehabilitation in these lines. On the bases of analyzed opportunities and best practices all possible alternative sceneries are given for reinforced concrete poles of transmission lines in the network. Multidisciplinary comparison is made for these alternatives and presented the advantages and disadvantages of each variant. The analysis pointed to solution - application of steel lattice towers instead of reinforced concrete. Project management of rehabilitation and reconstruction of the transmission line in the coming period will be a great deal with which will meet the engineers. However, an even greater engineering challenge will be deciding on the proper manner and dynamics of realization of projects for each line.
Keywords: Multi criteria Optimization; Reinforced concrete poles; economy; environment; Technology; recycling